Detecting Gravity-Related Misconceptions of First Year Medical Students Using the Newtonian Gravity Concept Inventory - Bani-Salameh, Hisham (Physics Education Research Journal, 2023)
Misconceptions create their problems and must be clarified. One of the misconceptions that often arises is the concept of Newtonian gravity. In this report, we discuss first-year medical students’ understanding of the concept of gravity examined using the Newtonian Gravity Concept Inventory (NGCI). Four domains of the concept of gravity are covered by the NGCI utilizing 26 multiple-choice questions: Directionality, Gravity as a force, Independence from other forces, and threshold. One of the goals of this study is to evaluate the effectiveness of our teaching materials and methods. Therefore, the test was given to students twice as a pre and post-test relative to in-class gravity-related instructions. In this article, we’re reporting on gravity-related misconceptions found with our students in the pre-test only. 511 students participated in the test with a recorded average score of 39.9%. We documented a complete list of misconceptions with eleven dominant ones found in the pre-test: Gravity is affected by magnetism, Gravity is affected by objects’ density, misconceptions related to the dependence of the force of gravity on the distance, and more.